Farmers’ Coping Strategies to Mitigate Acha Cultivation Challenges in Plateau State, Nigeria (UNIZIK Journal of Agricultural Economics and Extension, 2024)
Acha farming is laden with challenges across the value chain which could impact negatively on farmers socio-economic wellbeing. Thus, this study investigated the coping strategies employed to reduce Acha farming challenges among farmers in Plateau State. The population of this study comprised all the registered Acha farmers in two of the three agricultural zones in Plateau State. These two agricultural zones are Plateau North and Plateau Central with an estimated 3,143 registered Acha farmers according to Plateau Agricultural Development Programme (PADP). Out of the population, only 400 Acha farmers were randomly selected using Taro Yamane’s formula. The study adopted semi-structured questionnaire and data obtained were analysed with frequencies and percentages while the hypothesis was analyzed with the use of Pearson Product Moment Correlation (PPMC). Findings showed that the foremost challenges facing Acha farmers were inadequate harvesting equipment and high cost of labour (93.6%), lack of access to improved processing equipment and low-quality packaging sacks (90.5%). The highest ranked coping strategies employed by the farmers were to have adequate knowledge of climate condition (90.5%), use community cooperatives to reduce high cost of labour (89.4%), and belong to a cooperative to obtain a loan (74.7%). PPMC analysis showed that challenges encountered significantly influenced the coping strategies employed by the farmers in the positive direction (r=1.86; p
Keywords: Climate; Community Cooperatives; Condition; Coping Strategies; Socio-economic; Wellbeing